Editorial: Categorising Migrants: Standards, complexities, and politics - Meyer, Claus K.; Boll, Sebastian (Anti-Trafficking Review, 2018)
In spring 2017, New York Times correspondent Patrick Kingsley went to Turkey to cover the lives of Syrian refugees. In Istanbul, Kingsley met Abu Mohammed, a former surgeon’s assistant from Syria, who between 2015 and 2016 had helped to facilitate the passage of refugees from his home country into Greece. After narrowly escaping death in his own failed attempt to reach Europe, Mohammed had earned some USD 800,000 with ‘smuggling’ activities. He himself spoke of a ‘dirty business’, but it had also been more than just a business—the refugees whom he had helped reach Europe included relatives and even his own son. Kingsley also met 15-year-old Syrian Ismail Alanzi, a refugee working ‘up to 11 hours a day, six days a week’ on a farm in the east of Turkey—much more than the limit set by Turkish law for someone his age. With his father unable to find employment, however, the burden of supporting the family fell upon Ismail. He earned about TRY 800 (USD 225) per month for his toil, which was little more than half of the statutory minimum wage in the country. Ismail also received permission for his family to set up a tent on the land of his employer as they struggled to find proper housing. Turkish law restricts refugees to residing in the province where they are registered, but the family had moved in search of work.